2016
DOI: 10.1038/mi.2015.75
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 and probiotic therapy improve Th17 frequencies, microbial translocation, and microbiome in ARV-treated, SIV-infected macaques

Abstract: Increased mortality in antiretroviral (ARV)-treated, HIV-infected individuals has been attributed to persistent immune dysfunction, in part due to abnormalities at the gastrointestinal barrier. In particular, the poor reconstitution of gastrointestinal TH17 cells correlates with residual translocation of dysbiotic, immunostimulatory microflora across a compromised intestinal epithelial barrier. We have previously demonstrated that oral probiotics promote increased intestinal CD4+ T-cell reconstitution during A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 48 publications
2
76
1
Order By: Relevance
“…In addition, the authors observed improved functionality of antigen presenting cells (APCs) without overt DC activation, suggesting that innate immunity can also be enhanced by probiotic supplementation [70]. In a follow up study, ART-treated SIV-infected macaques were given a combination of probiotics and IL-21, which also improved frequencies of Th17 cells, potentially due to an observed decrease in Kyn:Trp ratios and decreased IDO activity in plasma [105**]. …”
Section: Therapeutic Approaches To Improve Microbiome and Microbial Tmentioning
confidence: 99%
“…In addition, the authors observed improved functionality of antigen presenting cells (APCs) without overt DC activation, suggesting that innate immunity can also be enhanced by probiotic supplementation [70]. In a follow up study, ART-treated SIV-infected macaques were given a combination of probiotics and IL-21, which also improved frequencies of Th17 cells, potentially due to an observed decrease in Kyn:Trp ratios and decreased IDO activity in plasma [105**]. …”
Section: Therapeutic Approaches To Improve Microbiome and Microbial Tmentioning
confidence: 99%
“…Th17 and Th22 cells, important components of mucosal immunity, are significantly depleted in HIV and SIV infection, and this depletion is associated with reduced barrier integrity, microbial translocation, and systemic immune activation (32)(33)(34). Previous studies have demonstrated a connection between commensal bacteria and the ability of probiotic therapy to enhance intestinal Th17 frequencies (15,35,36). Thus, we hypothesized that alteration of the microbiome through FMT might restore Th17 and Th22 frequencies.…”
Section: Increased Peripheral Th17 and Th22 Frequencies And Decreasedmentioning
confidence: 99%
“…ϩ T cell restoration in the GI tract after probiotic therapy or therapy with probiotics supplemented with interleukin-21 (IL-21) (15,16). In HIV-infected individuals, probiotics have been shown to decrease inflammation and microbial translocation (17,18).…”
mentioning
confidence: 99%
“…Few studies have been published on the role of a probiotic supplementation on SIV+ monkeys and on HIV+ humans, with promising results regarding the immune reconstitution of the gut barrier and immune response (Cunningham-Rundles et al, 2011;d'Ettorre, Ceccarelli, Andreotti, et al, 2015;d'Ettorre, Ceccarelli, Giustini, et al, 2015;Ortiz et al, 2016;Villar-García et al, 1999). No information is available on the effects of a probiotic supplementation on brain function and behavior of HIV+ subjects.…”
Section: Introductionmentioning
confidence: 99%